Body image dissatisfaction, depression, and anxiety in adolescents with celiac disease - Daldaban Sarıca, Buket; Demirci, Esra; Altay, Derya; Arslan, Duran (Frontiers in Pediatrics, 2025)
IntroductionCeliac disease, also known as gluten-sensitive enteropathy, is an immune-mediated disorder with a broad clinical manifestations including psychiatric symptoms. The present study aims to evaluate body image dissatisfaction, depression, and anxiety among adolescents with celiac disease and to draw attention to the diagnosis and management of these comorbidities.MethodsThis study was performed in Pediatric Gastroenterology unit of Erciyes University between July 2022 and June 2023. Adolescents aged 12–18 years diagnosed with histopathologically confirmed celiac disease and their age- and sex-matched healthy peers, were recruited in the study.ResultsA significant difference was found between the patient and control groups in depression (p < 0.001), and body image dissatisfaction (p < 0.001). Adolescents who were non-compliant with the diet showed significantly elevated risk of body image dissatisfaction and depression compared with participants who adhered to the strict diet (p = 0.001, p < 0.001, respectively). A positive correlation was observed between tTGA-IgA antibody levels and depression (r = 0.618; p < 0.01), and a negative correlation was found between tTGA-IgA antibody levels and body image dissatisfaction scores (r = −0.400, p = 0.014).ConclusionThe present results underscore adolescents with celiac disease are at an heightened risk for psychiatric burden. Therefore, periodic follow-up should be performed to determine body image satisfaction in adolescents with celiac disease and to recognize mood-related symptoms. Early identification of symptoms associated with mood disorders and body image dissatisfaction in adolescents is critical for efficient patient care within celiac disease and to enhance adolescents’ holistic well-being.